Ethics, anonymity and fictional distance: ‘Fictional critique’ applied to the study of heritage - Díaz Aguilar, Antonio Luis; Sánchez-Carretero, Cristina (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2020)
Fiction has been used as a tool for experimental ethnographic writing in an assiduous manner since the crisis of representation in anthropology since the 1980s. In this article we analyze a less discussed aspect of ethnographic fiction: the possibilities it offers to think, from another angle, the problem of the anonymity of the sources and the ethical responsibility towards the people who are the subjects of ethnographic research. Specifically, a fictional account is proposed to deal with the use of participatory processes in heritage management. The genre of "ficto-criticism" is considered as a methodological and political device that questions and reflects on social reality.